Lipidomic Modulation in Stressed Albino Rats Is Altered by Yolk and Albumen of Quail (Coturnix japonica) Egg and Poultry Feed - Oluwafemi Ibukun, Emmanuel (Biochem Res Int, 2016)
Cold and immobilization stressors can generate oxidative stress as well as skeletal muscle fatigue. Free radicals cause oxidative degradation of lipids, proteins, nucleic acids, and carbohydrates molecules, thereby compromising cell integrity and function. Quail egg had been described as being very functional biochemically, due to the essential biomolecules it contains in very regulated quantity. This study was aimed for evaluating the dietary effect of the egg on lipid profile parameters on selected tissues. The antilipidemic properties of the egg yolk and albumen and poultry (layers) feed were determined in selected tissues in male albino rats assaulted with cold immobilization stress induced on them at 4°C for 2 hours, while diazepam was used as standard antistress drug. Antilipidemic activities were evaluated by lipid profile modulation (HDL, LDL, TRIG., and T-CHOL.). Quantitative and qualitative analyses of fatty acids profile of the yolk hexane-extract were determined by Gas Chromatography and Mass Spectrophotometry (GC-MS). The ameliorative impacts of diazepam (2.5 and 5.0 mg/mL/kg BW), yolk (5 and 10 mL/kg BW), albumen (5 and 10 mL/kg BW), and the feed (5–10 mg/kg BW) were competitively (p < 0.05) specific for each of the tissues. The result of the study suggested yolk and albumen of quail egg and poultry feed as antistress agents as well as lipid modulators.